2000
DOI: 10.1034/j.1600-0773.2000.pto870601.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Amodiaquine Treatment on Microsomal Lipid Peroxidation and Antioxidant Defense Systems of Rats

Abstract: Abstract:The effects of single and multiple doses amodiaquine treatment on enzymatic and non-enzymatic antioxidant profiles and hepatic microsomal lipid peroxidation were investigated in rats. Treatment of rats with 10 mg/kg (single dose) amodiaquine resulted in 10% and 63% increases, respectively in the activities of liver superoxide dismutase and glutathione peroxidase (P∞0.01), while the activity of liver catalase was significantly reduced by 26% compared to control. The levels of serum vitamins A, C and b-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…This was confirmed by the study of Dass and Shah (2000) in which a marked elevation of transaminase levels was reported. Other antimalarials -amodiaquine (Farombi, 2000) and quinine (Debra and Megan, 1999) -were also reported to induce hepatic damage.…”
Section: Discussionmentioning
confidence: 96%
“…This was confirmed by the study of Dass and Shah (2000) in which a marked elevation of transaminase levels was reported. Other antimalarials -amodiaquine (Farombi, 2000) and quinine (Debra and Megan, 1999) -were also reported to induce hepatic damage.…”
Section: Discussionmentioning
confidence: 96%
“…SA postures are "risk-assessment" behaviour which indicate that the animal is hesitant to move from its present location to the new position (Blanchard et al, 2001), and thus high frequencies of these activities indicates high level of anxiety. AQ causes lipid peroxidation and induced agranulocytosis (Maggs et al, 1988;Farombi, 2000). These had earlier been reported to result in agitation, aggressiveness, confusion, personality changes and psychotic symptoms in chronic doses (Tester-Dalderup, 1984) and involuntary movements in acute usage (Salako, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…This has been implicated in lipid peroxidation (Maggs et al, 1988;Farombi, 2000). Peroxidation of lipid is responsible for damage to tissue in vivo (Mayes, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Other antimalaria agentsamodiaquine (Farombi, 2000) and quinine (Debra and Megan, 1999) -were also reported to induce hepatic damage. Farombi and Emerole (1998) reported that CQ increased the cholesterol/phospholipids ratio in microsomes, thereby disrupting the membrane fluidity and leading to an alteration in membrane function.…”
Section: Discussionmentioning
confidence: 96%